The m6A Dynamics of Profilin in Neurogenesis - Rockwell, Antonio L.; Hongay, Cintia F. (Frontiers in Genetics, 2019)
Our understanding of the biological role of N6-methyladenosine (m6A), a ubiquitous non-editing RNA modification, has increased greatly since 2011. More recently, work from several labs revealed that m6A methylation regulates several aspects of mRNA metabolism. The “writer” protein METTL3, known as MT-A70 in humans, DmIme4 in flies, and MTA in plants, has the catalytic site of the METTL3/14/16 subunit of the methyltransferase complex that includes many other proteins. METTL3 is evolutionarily conserved and essential for development in multicellular organisms. However, until recently, no study has been able to provide a mechanism that explains the essentiality of METTL3. The addition of m6A to gene transcripts has been compared with the epigenetic code of histone modifications because of its effects on gene expression and its reversibility, giving birth to the field of epitranscriptomics, the study of the biological role of this and similar RNA modifications. Here, we focus on METTL3 and its likely conserved role in profilin regulation in neurogenesis. However, this and many other subunits of the methyltransferase complex are starting to be identified in several developmental processes and diseases. A recent plethora of studies about the biological role of METTL3 and other components of the methyltransferase complex that erase (FTO) or recognize (YTH proteins) this modification on transcripts revealed that this RNA modification plays a variety of roles in many biological processes like neurogenesis. Our work in Drosophila shows that the ancient and evolutionarily conserved gene profilin (chic in Drosophila) is a target of the m6A writer. Here, we discuss the implications of our study in Drosophila and how it unveils a conserved mechanism in support of the essential function of METTL3 in metazoan development. Profilin (chic) is an essential gene of ancient evolutionary origins, present in sponges (Porifera), the oldest still extant metazoan phylum of the common metazoan ancestor Urmetazoa. We propose that the relationship between profilin and METTL3 is conserved in metazoans and it provides insights into possible regulatory roles of m6A modification of profilin transcripts in processes such as neurogenesis.